Psychosocial correlates of academic burnout among university students in Singapore - Leong, Xueheng (2017)
Limited studies have been done on academic burnout. This study aims to identify the potential predictors of academic burnout – some of which are individual differences such as personality traits while others are behavioral factors such as coping mechanisms when faced with stressors – of academic burnout in university students. University students in Singapore were recruited to complete a series of questionnaires to gather information about the (a) time management styles, (b) burnout levels, (c) coping strategies, (d) achievement motives and (e) academic motivation of the respondents. Factor analysis found three dimensions of academic burnout similar to past research. Multiple regression analysis results suggested that emotional exhaustion can be predicted by amotivation and fear of failure, cynicism can be predicted by amotivation, intrinsic motivation and fear of failure, and personal efficacy can be predicted by amotivation, intrinsic motivation, hope of success, adaptive coping strategies and better time management practices. Implications will be discussed, and future studies can build on the predictors found by this study to aid in understanding, preventing and reducing academic burnout.